Lā an-Nāhiyah fī Surah al-Kahfi wal-Qiyam at-Tarbawiyyah al-Mutadammanah fīhā - Ainul Zahidah; Fahmi Ridha (Mauriduna: Journal of Islamic Studies, 2023)
تهدف هذه الدراسة إلى معرفة عدد الآية "لا" الناهية في سورة الكهف وتهدف كذلك إلى معرفة القيم التربوية في الآيات المتضمنة في "لا" الناهية في سورة الكهف. إن هذه الدراسة تسلك منهج الوصفي، وذلك بتتبع "لا" الناهية في سورة الكهف والقيم التربوية المتضمنة فيها ، وجمعها، وتصنيفها، وعرضها والاستنتاج. هذه الدراسة وجدت "لا" الناهية في سورة الكهف أحد عشر )11( موضعا، ووجدت عدة القيم التربوية المتضمنة في "لا" الناهية في سورة الكهف، والقيم المتضمنة فيها فهي النهي عن الشرك، والنهي عن الجدال والاستفتاء الذي لا يعرف حقيقته، والنهي عن التحكم بالأمر المستقبل، وطاعة أمر الله تعالى، وطلب الاعتذار The purpose of this research is to know numbers of verses contained prohibition letter “ La an-Nāhiyah ” in surah al-Kahfi and to know educational values in this probihition. The study uses descriptive method, namely by tracing the terms “Lā an-Nāhiyah” in surah Al-Kahfi, collecting data, classifying data, expose data and analyzing educational values in this prohibition, and conclusions data. This study explains “Lā” an-Nāhiyah in surah Al-Kahfi found in eleven (11) positions, and with many educational values of its. The following educational values are the prohibition of associating partners with Allah, the prohibition of arguing and referendums that do not know the truth, and the prohibition of controlling the future matter, and obeying an order God Almighty, and asked for an apology. Penelitian ini bertujuan untuk mengetahui jumlah “Lā” an-Nāhiyah dalam surat al-Kahfi dan untuk mengetahui nilai-nilai pendidikan yang terkandung didalamnya Metode penelitian yang digunakan adalah metode analisis deskriptif, dengan langkah-langkah mengumpulkan data tentang “Lā” an-Nāhiyah dalam surat (Al-Kahfi), serta pengklasifikasian data, pemaparan data dan nilai-nilai pendidikan yang terkandung dalamnya, dan kesimpulan data tersebut Kajian ini menemukan “Lā” an-Nāhiyah dalam surat Al-Kahfi ada sebelas (11) tempat, penelitian ini juga mendapatkan beberapa nilai pendidikan yang terkandung dalam ayat tersebut, nilai pendidikan tersebut adalah larangan menyekutukan Allah, larangan berdebat dan musyawarah yang tidak diketahui kebenaran, larangan memastikan urusan yang akan datang, mentaati perintah Allah SWT, dan meminta permintaan maaf